Not all fine-branch locomotion is equal: Grasping morphology determines locomotor performance on narrow supports. Issue 142 (May 2020) - Young, Jesse W.; Chadwell, Brad A.
Abstract: Fine-branch models have long played a central role in primate evolutionary research. Nevertheless, recent studies of positional behavior in nonprimate arboreal mammals have challenged the idea that synapomorphic primate features, such as grasping extremities, uniquely facilitated access to the fine-branch zone. We test the alternative hypothesis that grasping extremities specifically improve locomotor performance in a fine-branch environment by examining how support diameter influences locomotor mechanics in one sciurid rodent ( Sciurus carolinensis ) and two platyrrhine primates ( Callithrix jacchus and Saimiri boliviensis ). These species were chosen to broadly model different stages in the evolution of primate grasping morphology. The results showed that transitioning from broad to narrower supports required the greatest kinematic adjustment in squirrels and the least adjustment in squirrel monkeys, with marmosets displaying an intermediate level of adjustment. Moreover, on any given support, squirrels' locomotor mechanics differed from marmosets' in a manner consistent with a greater need for stability, despite superficial ecomorphological similarities between sciurid rodents and callitrichine primates. Morphological analyses of autopodial size and proportions suggest that variation in locomotor performance more closely tracked variation in overall hand and foot size rather than digit length per se. Indeed, a broad comparative analysis revealed that for their body mass, primates have longer hands than similarly sized arboreal rodents and marsupials (although only the primate-rodent comparison was significant after incorporating phylogenetic relatedness). Inclusion of fossil stem primates (plesiadapiforms) and euprimates (adapiforms) in these analyses suggests that this primate-wide grade shift in relative autopodial size must have occurred early in the evolutionary history of the group. Overall, our findings show that basal primate morphological adaptations may have specifically facilitated improved locomotor performance in a fine-branch niche, rather than merely permitting access to the environment. As such, future adaptive hypotheses of primate origins should incorporate the import of primate-like morphology on locomotor performance as well. Highlights: Fine-branch models have long played a central role in primate evolutionary research. Recent studies of arboreal locomotion in nonprimates have challenged this view. We show that grasping improves fine-branch locomotor performance. Models should include impact of grasping on performance, not just fine-branch access.